Ethnobotanical knowledge of Dayak Ngaju in utilizing plant species to locate gold mining in Sei Riang Village, Central Kalimantan, Indonesia - SITI SUNARIYATI; DECENLY DECENLY; ANDI RIANG PURNAMA; RETNO AGNESTISIA (Society for Indonesian Biodiversity, 2023)
Abstract. Sunariyati S, Decenly, Purnama AR, Agnestisia R. 2023. Ethnobotanical knowledge of Dayak Ngaju in utilizing plant species to locate gold mining in Sei Riang Village, Central Kalimantan, Indonesia. Biodiversitas 24: 4145-4150. Indonesia is one of the richest countries in flora and cultural diversity. The strong relationship between the culture and plant diversity has developed ethnobotanical knowledge of the indigenous community, including the knowledge of the Dayak Ngaju Tribe in utilizing plant species as gold indicators. Therefore, this study aimed to inventory and identify the plant species used as gold indicators by Dayak Ngaju in Sei Riang Village, Gunung Mas District, Central Kalimantan, Indonesia using ethnobotanical study and then empirically assess the gold content in the identified plants using laboratory analysis. Ethnobotanical information was collected through in-depth interviews with 25 informants and analyzed with the Informant Agreement Ratio (IAR). Plants mentioned as gold indicators were then identified in the field. The samples of the plants were then examined by atomic absorption spectroscopy to determine gold (Aurum; Au) contents in their root, stem, and leave tissues. The data was analyzed using SPSS 25 with the Parametric Pearson Correlation test to determine the correlation and significance level of Au contents found in the plant tissues and soil. Based on the interview results, the gold miners believed that several plant species could be utilized to indicate gold’s presence in the mining area, as indicated by the value of IAR of 0.540, suggesting that 54% of the informants agreed to use the plants as the gold indicator. Two plant species were identified as gold indicators: Kasuhui (Dipterocarpus sp.) and Hara (Ficus racemosa L.). Significant positive correlations were also exhibited between Au contents in the Kasuhui stem and the Hara root and stem and the soils where they grow. This research is expected to promote the ethnobotanical knowledge of the gold miners from the Dayak Ngaju Tribe in selecting scientifically justifiable gold mining areas.